PEMBERDAYAAN PEREMPUAN MARGINAL MELALUI PROGRAM PENDIDIKAN KECAKAPAN HIDUP-PEREMPUAN (PKH-P) - A. Suhardi (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This paper describes the empowerment of marginal women through women's life skill education program. Lack of access to education, economy, employment, public policy, basic rights, gender equality, politics, and health are the causes of women getting marginalized. Empowering women through life skills education are an effort to empower women through various activities. The result of program â€œPKH-P (Pendidikan Kecakapan Hidup-Perempuanâ€ is behavior change, that is the increasing of knowledge, skill, and attitude of self. So that marginal women can help themselves to be more empowered and out of the condition of their marginality towards the quality of life and higher level of living welfare.